PROMOTING QUALITY METADATA IN LIBRARIES:THE ROLE OF EDUCATION - Harvey, Ross (Malaysian Journal of Library and Information Science, 2003)
This paper considers the current state of education for bibliographic organisation, considered broadly and encompassing descriptive cataloguing, subject access, classification, metadata, knowledge organisation, bibliographic control and other related areas for all formats of library resources. In it, Australia is used as a case study. Data comes from subject and course descriptions located in the handbook entries and web sites of Australian university-level programmes in library and information studies. Conclusions are drawn about the range of subjects taught, their focus, and their levels. The paper also considers some aspects of teaching bibliographic organisation by distance education, a mode rapidly becoming the norm for students enrolled in library and information science courses, and notes some of the issues associated with teaching bibliographic organisation in this mode.